If it's not what You are looking for type in the equation solver your own equation and let us solve it.
86=2(3+5n)
We move all terms to the left:
86-(2(3+5n))=0
We add all the numbers together, and all the variables
-(2(5n+3))+86=0
We calculate terms in parentheses: -(2(5n+3)), so:We get rid of parentheses
2(5n+3)
We multiply parentheses
10n+6
Back to the equation:
-(10n+6)
-10n-6+86=0
We add all the numbers together, and all the variables
-10n+80=0
We move all terms containing n to the left, all other terms to the right
-10n=-80
n=-80/-10
n=+8
| 23y=(2+4=) | | 8(5k-5)+6(7k-3)=24 | | -2-3b=b+6 | | 4=a+16 | | 86=-2(6-7x) | | 6x/4+4=x+6 | | -9-(9x-6)=(3(4x+6) | | x^2-7x+54=0 | | x=8000(1.06)^9 | | 68=10x+x^2 | | 2(x−3)=−3(x+5)−6 | | (2b-4)2=(b-1) | | (2b-4)2=(b-1 | | k7=k+18 | | 4x/2=15/2 | | 20x+12x-10x=44 | | 19^2=100+x^2 | | 15y+16=20 | | 6x=378 | | 2x^2(x+2)-4=8 | | 5x/9+20/5=22/6 | | 5/9x+20/5=22/6 | | 15=7e+1 | | 4y-7+4y-7+90=180 | | f(10)=34 | | 4x+6+2x=2+3x | | 6m-15=-27 | | -5(x+5)+29=10-6x | | 8(1+3n)+3n=89 | | 3x^2−36x=−42 | | 5y/6+2=30 | | 17n-20n=81 |